Hidden Wisdom in Purity and Modern Medical Science: طہارت میں پوشیدہ حکمتیں اور جدید میڈیکل سائنس - Iqbal, Dr. Farzana; Tirmazi, Ruqyyah (Al Khadim Research Journal of Islamic Culture and Civilization, 2021)
Attempts to highlight the element of purity and purity in the Islamic way of life have not been made in any other religion. The cleansing obtained from impurity, filth and impurity which is in accordance with the Shariah principles is called Taharat. Islam has also asked its followers to adopt purity and has mentioned its virtues and importance and its promises. Islam incorporated the purity and cleanliness of the body into the nature of man.A person who does not respect prayers.It is called purity, chastity, purity and cleanliness.Purity also has many beneficial and positive effects on a person's individual life.